2011
DOI: 10.1051/0004-6361/201116705
|View full text |Cite
|
Sign up to set email alerts
|

The fratricide ofαΩ dynamos by theirα2siblings

Abstract: Context. Helically forced magneto-hydrodynamic shearing-sheet turbulence can support different large-scale dynamo modes, although the αΩ mode is generally expected to dominate because it is the fastest growing one. In an αΩ dynamo, most of the field amplification is produced by the shear. As differential rotation is an ubiquitous source of shear in astrophysics, such dynamos are believed to be the source of most astrophysical large-scale magnetic fields. Aims. We study the stability of oscillatory migratory αΩ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…In that gauge, magnetic helicity evolves merely like a passive scalar. Numerical experiments confirm that, within error bars, there is no magnetic helicity flux in situations where the formula for the VC flux would have predicted one (Hubbard & Brandenburg 2010b).…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…In that gauge, magnetic helicity evolves merely like a passive scalar. Numerical experiments confirm that, within error bars, there is no magnetic helicity flux in situations where the formula for the VC flux would have predicted one (Hubbard & Brandenburg 2010b).…”
Section: Resultsmentioning
confidence: 53%
“…It should also be noted that the theoretical foundations of the VC flux have been called into question (Hubbard & Brandenburg 2010b). The criticism is connected with the fact that a shear produces spurious divergences of magnetic helicity flux that can only be removed in a gauge where the scalar potential is equal to the dot product of velocity and vector potential.…”
Section: Resultsmentioning
confidence: 99%
“…On this occasion we mention that, using the same setup as here, Hubbard et al (2011) have demonstrated that, after some initial saturation phase, the aW dynamo mode is "fratricided" by a separate 2 a mode and eventually the initial aW model µ -dependence, whereas blue dotted line represents Equation (8). The data points for initial growth phase (t 0.6 diff t < ) are not used for this plot.…”
Section: Large R M and Large D: Regime Ivmentioning
confidence: 76%
“…Recently, Mitra et al (2010) reported an intriguing numerical finding in their forced helical turbulence that α 2 dynamo can yield solar-like equatorward migration of magnetic activity belts (see also Schrinner et al 2011). The superiority of the α 2 mode over αΩ mode at the nonlinear stage was found by Hubbard et al (2011). Furthermore, a connection between α 2 dynamo mode and solar magnetism was suggested in some recent results of global MHD dynamos (e.g., Simard et al 2013;Käpylä et al 2013b).…”
Section: Summary and Discussionmentioning
confidence: 96%